2022
DOI: 10.1101/2022.02.10.479822
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

sgcocaller and comapr: personalised haplotype assembly and comparative crossover map analysis using single-gamete sequencing data

Abstract: Profiling gametes of an individual enables the construction of personalised haplotypes and meiotic crossover landscapes, now achievable at larger scale than ever through the availability of high-throughput single-cell sequencing technologies. However, haplotyping single gametes from high-throughput single-cell DNA sequencing datasets using existing methods requires intensive processing. Here we introduce an efficient software toolset using modern programming languages for the common tasks of haplotyping haploi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…1c). To call crossovers using single-sperm sequencing data and downstream analyses, we developed an open-source bioinformatic tool kit containing sgcocaller and comapr [76] (see Materials and Methods). Consistent with the bulk sequencing and PCR-based methods, an increase in total crossover frequency and map length was observed in Fancm Δ 2/ Δ 2 compared to Fancm +/+ (p = 0.001, permutation test (B = 1,000), 1,347 cM and 1,178 cM, respectively)(Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1c). To call crossovers using single-sperm sequencing data and downstream analyses, we developed an open-source bioinformatic tool kit containing sgcocaller and comapr [76] (see Materials and Methods). Consistent with the bulk sequencing and PCR-based methods, an increase in total crossover frequency and map length was observed in Fancm Δ 2/ Δ 2 compared to Fancm +/+ (p = 0.001, permutation test (B = 1,000), 1,347 cM and 1,178 cM, respectively)(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Output files from sgcocaller are further parsed and analysed for crossover interval identification and crossover profile comparison. With the sequence of hidden states inferred, the crossover interval locations were called by applying functions implemented in R package comapr [76]. The construction of genetic distance maps and crossover distributions were also performed using comapr .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that IIIandMe , which applies to genomic data of high quality, can accurately infer chromosomal haplotypes using three or a few more single gametes and is computationally much more efficient than Hapi . Given that crossovers are very rare (Beye et al 2006; Lyu et al 2022), three gametes are theoretically sufficient for phasing the entire genome, likely pushing the boundary to its possible limit. We foresee that IIIandMe will find its way to become impactful in many genetic research areas and applications.…”
Section: Main Textmentioning
confidence: 99%
“…Sperm can be used with genomic technologies to study diverse topics such as fertility, genome structure and forensic science [1][2][3][4][5]. A major challenge for the isolation of individual haploid cells from males for sequencing is that they stick to most pipette tips and tubes, and traditional methods for bulk sperm isolation use technically challenging density gradients.…”
Section: Introductionmentioning
confidence: 99%